An updated review on systemic glucocorticoids in the prevention and treatment of bronchopulmonary dysplasia - Xinyi Wang; Yuan Shi (Wiley, 2023)
Abstract Bronchopulmonary dysplasia (BPD) is a severe chronic pulmonary disease affecting premature infants and their families. The main pathogenesis of BPD is the abnormal inflammatory response in immature lungs, resulting in the distortion of lung development and influencing the formation of alveoli and vascular structures. Based on anti‐inflammatory mechanisms, glucocorticoids may reduce the incidence and mortality of BPD in premature infants, but different types and administrations of glucocorticoids may lead to various short‐term or long‐term outcomes, especially the most concerning neurodevelopmental abnormalities. Dexamethasone is currently recognized as a first‐choice drug for BPD, but the different administration methods may affect the efficacy and safety of the regimen. Hydrocortisone is currently considered to minimize both short‐term and long‐term adverse outcomes, but its effectiveness needs to be confirmed by further trials. Numerous alternative strategies have been proposed to reduce adverse reactions, such as moderate early dosing, lower cumulative doses, and individualized dosing, but the high‐quality evidence is still not enough. This review is trying to summarize some new developments in mechanisms of action, adverse effects, and other treatment regimens of systemic glucocorticoids for the prevention and treatment of BPD in the recent few years.